Metformin degradation with catalytic ozonation - Tan, Yu En (Nanyang Technological University, 2021)
In 2019, there are approximately 463 million adults suffering from diabetes and the number is only expected to increase in the future. Amongst the diabetic patients, almost 90% are identified to be Type 2 diabetes patients, who consumes primarily Metformin as a treatment drug. However, studies have shown that a 90.5% of the initial Metformin dose consumed by patients are found in their urine sample after 24 hours. Conventional wastewater treatment processes do not cater to the removal of Metformin; thus, trace amount is still detected in surface waters, which are usually source of drinking water supplies. Metformin is considered an endocrine disrupting compound as it has been observed to cause abnormal hormonal activities in aquatic species such as fathead minnow fish. Furthermore, it can bioaccumulate and hence posing risk to human health and aquatic ecosystem. Therefore, it is urgent to treat Metformin in wastewater treatment processes. Many studies on removal of Metformin from wastewater involve advanced oxidation processes (AOPs), such as irradiation and ozonation, but no study has been carried out to degrade Metformin via combined catalytic ozonation. Therefore, this project investigates catalytic ozonation on the degradation of Metformin, with Cerium Oxide (CeO2) as the catalyst. The results are obtained through an UV-visible spectrophotometer, where the concentrations of Metformin and the rate of degradation will be analysed, Throughout the experiments, parameters such as the initial concentration of Metformin and catalyst, ozone feed rate, and pH levels will be varied to evaluate their effect on the degradation efficiency. The results shows that complete Metformin degradation cannot be achieved for all initial concentrations studied (1-5 mg/L), the maximum degradation achieved is 69.4% and 44.4% for 1 and 5 mg/L metformin concentration. It is also found that catalyst enhances the degradation of Metformin substantially (c.f. 31.3% degradation with only ozone vs 82.8% degradation at 20 mg/L CeO2 catalyst). Increasing catalyst loading will increase the degradation efficiency. The experimental data also show that increasing the initial Metformin concentration will lead to a decrease in Metformin degradation. Interestingly, varying ozone feed rate does not show a significant change in the rate of degradation of Metformin. It has also been found that at pH 10, there will be a faster rate of degradation of Metformin, compared to a lower pH condition of pH 3. With a higher initial concentration of catalyst added into the solution, the rate of degradation of Metformin will increase, as there are more hydroxyl radicals available for reaction to occur. In conclusion, this project reveals that catalytic ozonation is a more effective method to degrade Metformin as it can significantly enhance the degradation of Metformin by more than two-fold.